Deadly Decisions - Kathy Reichs (UK William Heinemann Ltd., 2000)
Emily Anne Toussant, nine years old, is shot dead on a Montreal street. A North Carolina teen disappears and parts of her skeleton are found hundreds of miles away. For forensic anthropologist Tempe Brennan, the deaths act as a catalyst, propelling her deep into the culture of outlaw motorcycle gangs where one misstep could bring disaster.
Keywords: Literature (3GdCOHs; Brennan, Temperance (Fictitious character) -- Fiction; General; Women forensic anthropologists -- Fiction